Isolation and the "epidemic" of melancholy in the Early Modern Europe: : A cultural approach to melancholy - G. Leontsini, Maria-Konstantina (Maritina) (Mos Historicus: A Critical Review of European History, 2023)
This paper is looking at the ‘epidemic’ of melancholy in early modern Europe. The dialogue of Stefano Guazzo Civil Conversation (Venice 1574) is taken as a case study as well as its dissemination in Europe. More specifically, it investigates the problem of isolation as the cause of the malady of melancholy. Furthermore, it indicates that melancholy could be cured through friendship and conversation, especially that between men and women. Friendship was viewed as milestone for the well-being of one person but also for the society as a whole. The issue of company and conversation is being viewed within court and civil culture and the key to social equilibrium and the cure to melancholy.